The Students’ Response Toward Indirect Corrective Feedback Used By The Lecturer In Teaching Writing At Cokroaminoto Palopo University - Ardhy Supraba; Musfirah Musfirah; Rizal A.M. Sjachrun; Edi Wahyono (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
This research aims to find out the students’ response toward indirect corrective feedback used by the lecturer in teaching writing. This research was conducted at Cokroaminoto Palopo University in class VIA. This research applied descriptive quantitative method. There are 9 students as the sample of this research taken by purposive sampling technique. The result of this research shows that the mean score of students’ response is 35.5. It means that students’ response toward indirect corrective feedback used by the lecturer in teaching writing at Cokroaminoto Palopo University is very negative. It indicates that the null hypothesis (H0) is accepted and the alternative hypothesis (H1) is rejected. It means that the indirect corrective feedback used by the lecturer in teaching writing does not give a positive response to students. Keywords: